Pengaruh Ukuran Perusahaan, Leverage, Dan Profitabilitas Terhadap Nilai Perusahaan : Studi Kasus Perusahaan Manufaktur SubSektor Logam Di BEI Tahun 2019-2023 - Anila Ambarani; Kasmanto Miharja; Adella Yudanti; Verliana Diva (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
One of the company's goals is to maximize the value of its shares to achieve company value. When investing in the capital market, investors also take into account the value of the company. Over the last five years, the value of companies in the food and beverage subsector experienced a significant decline from 2020 to 2023. This decline began in 2019. Many factors, including company size, profitability and leverage, influence the value of a company. The gap phenomenon supports the existence The research gap indicates the need for additional research into the variables that influence firm value. The aim of this research is to present empirical data regarding the influence of company size, profitability and leverage on manufacturing companies in the metal industry and similar industries listed on the Indonesia Stock Exchange between 2019 and 2023. All companies in the food sector and beverage subsector are listed on the Exchange. Indonesian Securities (BEI) is the research population. A purposive sampling strategy was used to select the research sample from seven observations. Multiple linear regression analysis is used in research to analyze secondary data. SPSS is a program used in research. The findings of this research show how leverage and company size affect company value. However, empirical data also shows that profitability has little effect on company value. Simultaneously, the factors Company Size, Profitability, and Leverage influence Company Value.